German Universities Woo International Students - Morris-Lange, Simon; Schu, Cornelia (International Higher Education, 2020)
In Germany, universities in certain areas are facing challenges due to shrinking domestic enrollments. Other universities across Germany and in other European countries will soon be confronted with the same problems. Universities and their partners should provide international students with more flexible options for accessing higher education, as well as relevant support during their studies and in their transition from study to work.